Comparison between Eurocode 7 and British Standard in pile design under mixed ground condition - Feng, Jing (2013)
Pile foundation is extensively used in Singapore construction projects. Pile foundation axial capacity is designed based on the soil property, namely clayey/ silty soil, sandy soil and rock.